Gaming with health misinformation: a social capital-based study of corrective information sharing factors in social media - Feng, Bobo (Frontiers in Public Health, 2024)
Correction is an important tool to reduce the negative impact of health misinformation on social media. In the era of “I share, therefore I am” social media, users actively share corrective information to achieve the “anti-convincing” effect of health misinformation. Focusing on the local Chinese context, this study constructs a structural equation model using social capital as a mediating variable to explore whether usage of Chinese users’ social media can promote corrective information sharing by influencing the structural, cognitive, and relational dimensions of social capital and the role of health literacy in corrective information sharing. It was found that social media use did not significantly affect corrective information share willingness but significantly influenced share willingness through social interaction connections, trust, and shared experiences, and share willingness significantly influenced sharing behavior. The moderating effect showed that health literacy played a significant moderating effect in the influence of corrective information share willingness on sharing behavior. This study introduces the three dimensions of social capital at the theoretical level and finds that users will share corrective information for the purpose of social capital accumulation. It also provides empirical evidence for specific practices, including improving users’ health literacy and actively mobilizing them to participate in the blocking and management of health misinformation in social media.